IMPACT OF SMALL BUSINESS INNOVATION ACTIVITY ON REGIONAL ECONOMIC GROWTH IN RUSSIA - Nikitin, Alexander; Klimentova, Elvira; Dubovitski, Alexander (Revista Inclusiones, 2020)
The paper deals with studying how small business and its innovative activity actually affect the volume of the regional economy and its growth in modern Russian reality. Statistical information such as indices and indicators of economy state and development in the regions of the Russian Federation for 2011-2018 was used for assessment. It is safe to conclude that the level of gross regional product is most influenced by the expenditures on research and development; the volume of sales of innovative goods, works, services, turnover of small enterprises; the share of small enterprises that implemented technological innovations; the cost of technological innovations of small enterprises. The efficiency of regional economy depends on the total efficiency of all its economic entities. It is important to ensure the productivity of small businesses and their contribution to the gross regional product in relative terms at a level not lower than that of the average or the large businesses.